(3JgPjH GdCSeGA hGddZGJs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg HJQLeI (B: (3aVjd Hf YjGV Hf eSYhO Hbhdg (B: (3CHj YHO Gddg GdHNGQi ai JGQjNg hGHf CHj ai JGQjNg hGHf CHj MGJe ai GdLQM hGdJYOjd s
(3BNQgG (B:s
(3ef cJGH GddZGJ (B: (3GdMjQI hNi eOjfI eYQhaI YfO GdchaI hgj eOjfI GdfYeGf BNQ MQa GdMGA jJdhg ai GdKGdK Ef TGA Gddg JYGdi MQa GdNGA ef aVd GddZI s
(3HgG fXGe GdJYbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs